Endothelial Dysfunction and Impaired Neurovascular Coupling Responses Precede Cognitive Impairment in a Mouse Model of Geriatric Sepsis - Csipo, Tamas; Cassidy, Benjamin R.; Balasubramanian, Priya; Drevets, Douglas A.; Ungvari, Zoltan I.; Yabluchanskiy, Andriy (Frontiers in Aging Neuroscience, 2021)
Sepsis is a life-threatening condition, the incidence of which is significantly increased in elderly patients. One of the long-lasting effects of sepsis is cognitive impairment defined as a new deficit or exacerbation of preexisting deficits in global cognition or executive function. Normal brain func-tion is dependent on moment-to-moment adjustment of cerebral blood flow to match the increased demands of active brain regions. This homeostatic mechanism, termed neurovascular coupling (NVC, also known as functional hyperemia), is critically dependent on the production of vasodila-tor NO by microvascular endothelial cells in response to mediators released from activated astro-cytes. This goal of this study was to test the hypothesis that sepsis in aging leads to impairment of NVC responses early after treatment and that this neurovascular dysfunction associates with im-pairments in cognitive performance and vascular endothelial dysfunction. To test this hypothesis, we used a commonly studied bacterial pathogen, Listeria monocytogenes, to induce sepsis in ex-perimental animals (males, 24 months of age) and subjected experimental animals to a standard clinical protocol of 3 doses of ampicillin i.p. and 14 days of amoxicillin added to the drinking. NVC responses, endothelial function and cognitive performance were measured in septic and age-matched control groups within 14 days after the final antibiotic treatment. Our data demonstrate that sepsis in aging significantly impairs NVC responses measured in somatosensory cortex during whisker stimulation, significantly impairs endothelial function in isolated and pressure cannulated aorta rings in response to acetylcholine stimulation, and shows a trend toward the impairment of cognitive function measured using the PhenoTyper home cage based system. Our findings suggest that sepsis-associated endothelial dysfunction and impairment of NVC responses may contribute to long-term cognitive deficits in older sepsis survivors.